Do Gold Prices Influence Generation Z’s Investment Motivation? Evidence from Indonesia - Habbe, Abdul Hamid; Mediaty; Sakinah, Andi Nur; Wahid, Abdul; Mallisa, Amalia Indah Pratama; Damara, Mochamad Rizky (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study investigates the influence of gold price perceptions on investment motivation among Generation Z in Indonesia. Adopting a behavioral perspective, the research applies the Theory of Planned Behavior (TPB) to explain how external economic signals such as gold price changes shape investment intentions. A quantitative explanatory design was used, with data collected from 62 Gen Z respondents through purposive sampling. Respondents completed a structured online questionnaire with items adapted from prior validated studies. Results of a simple linear regression analysis reveal that gold prices are significantly associated with increased investment motivation (R² = 0.392; p < 0.001), explaining 39.2% of the variance. These findings highlight the role of perceived financial stability and safe-haven value in shaping youth investment preferences. The study contributes to behavioral finance by providing empirical insights into Gen Z’s decision-making drivers in emerging markets. Implications are discussed for financial educators, policymakers, and digital investment platforms seeking to promote informed investment behavior among young adults.